2019
DOI: 10.3390/cancers11101600
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscape of the BAP1 Locus Reveals an Intrinsic Control to Regulate the miRNA Network and the Binding of Protein Complexes in Uveal Melanoma

Abstract: The BAP1 (BRCA1-associated protein 1) gene is associated with a variety of human cancers. With its gene product being a nuclear ubiquitin carboxy-terminal hydrolase with deubiquitinase activity, BAP1 acts as a tumor suppressor gene with potential pleiotropic effects in multiple tumor types. Herein, we focused specifically on uveal melanoma (UM) in which BAP1 mutations are associated with a metastasizing phenotype and decreased survival rates. We identified the ubiquitin carboxyl hydrolase (UCH) domain as a maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Sharma et al analyzed the mutational landscape of the BAP1 locus in the context of binding sites for miRNA. They showed that either germline or somatic mutations can affect the mRNA binding region located within the locus, which leads to disruption of the whole regulatory network, not only in uveal melanoma, but also in several other cancers [47]. Several different miRNAs were shown to influence BAP1 function in cervical cancer, renal carcinoma, lung cancer, breast cancer, and others [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Sharma et al analyzed the mutational landscape of the BAP1 locus in the context of binding sites for miRNA. They showed that either germline or somatic mutations can affect the mRNA binding region located within the locus, which leads to disruption of the whole regulatory network, not only in uveal melanoma, but also in several other cancers [47]. Several different miRNAs were shown to influence BAP1 function in cervical cancer, renal carcinoma, lung cancer, breast cancer, and others [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a large number of studies that have addressed the local/global DNA methylation changes in multiple human cancers and other diseases [11,15,16], the key link showing the switch towards the dynamics of DNA hypo-/hypermethylation is still missing. Perhaps, defining the distinct roles of hypo-and hypermethylation within the same individual might help to undermine their potential consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, inversions in the vicinity of the hotspot region in lower hominoids were also found. Apart from this, some genes were also found to be duplicated during evolution, as previously described . Due to widespread genomic rearrangements within the genome of gibbons, it was cautiously not incorporated into this study.…”
Section: Discussionmentioning
confidence: 88%
“…This is also evident from the clinical spectrum as BAP1 is the only gene of the hotspot region that is known to be mutated in UM, whereas genes such as BAP1 , PBRM1 , and SETD2 are frequently involved in renal cell carcinoma. Recently, we showed the altered expression of the BAP1 gene in 29 cancer types . In addition, we showed that C‐terminal BAP1 mutations have a stronger intrinsic control to regulate the miRNA network and the binding of subsequent protein complexes.…”
Section: Discussionmentioning
confidence: 98%